The effect of topping and various cytokinin-based plant growth regulators applications on immature Liberica coffee growth - Maxiselly, Yudithia; Samuel, Joshua; Suherman, Cucu (Universitas Padjadjaran, 2025)
The growth of Liberica coffee in the 2-year immature plant phase can be improved by applying cytokinin-based plant growth regulators (PGRs) and topping. Toppings applied to plants can inhibit apical dominance, while cytokinin PGRs such as 6-Benzylaminopurine (BAP) and coconut water can stimulate plant shoot growth. This research aims to determine the effect of topping and PGR application on the vegetative growth of Liberica coffee plants. This experiment was carried out at the Ciparanje experimental field, Universitas Padjadjaran, West Java, with an elevation of ± 750 meters above sea level from March to June 2024. The experimental design used a randomized block design with six treatments: control (no topping and no added PGR), topping, topping + 60 ppm BAP, topping + 50% coconut water, 60 ppm BAP, and 50% coconut water. Each treatment was repeated four times. The results showed the best results were (a) topping treatments (topping, topping+coconut water, and topping+BAP) on canopy width and primary branch length; and (b) a combination of 50% coconut water and 60 ppm BAP on increasing the number of branches. This study provides information on efficient maintenance methods for Liberica coffee plant growth in the immature phase.